Effect of intraocular lens implantation on combined extracapsular cataract extraction with trabeculectomy: a comparative study. Issue 10 (October 1988) - Neumann, R; Zalish, M; Oliver, M
Abstract : In an attempt to assess the effect of posterior chamber intraocular lens (IOL) implantation on the outcome of combined extracapsular cataract extraction (ECCE) and trabeculectomy we compared 23 eyes subjected to ECCE and trabeculectomy with 23 eyes subjected to a triple procedure-that is, with the addition of IOL implantation. The results showed that IOL implantation did not have a detrimental effect on postoperative IOP reduction, gain in visual acuity, or needs for antiglaucoma medication. The incidence of anterior chamber reactions consisting of the development of posterior synechiae and fibrin formation was significantly higher when IOL had been implanted. However, the fibrin was generally absorbed within 14 days and the posterior synechiae did not occlude the visual axis. We conclude that IOL implantation should be included in these combined operations with the object of rehabilitating visual function.